2006
DOI: 10.1111/j.1445-2197.2006.03667.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Thyroid Carcinoma in a Large Series of Consecutive Patients Operated on for Benign Thyroid Disease

Abstract: The results confirm the high frequency of ITC. ITC was more frequent in euthyroid patients than in thyrotoxic patients (P < 0.03). Sex, age, thyroid volume and interval between diagnosis and surgery did not significantly influence its incidence. The majority of ITC was represented by microcarcinomas, but in approximately 25% of patients, the tumour size was greater than 2 cm. The role played by FNAC in excluding malignancies proved to be fairly inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
3
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 23 publications
10
92
3
12
Order By: Relevance
“…The time of diagnosis of hyperthyroidism to thyroidectomy was not diff erent. However, Miccoli et al reported that, the diagnosis of incidental thyroid carcinoma in patients who were operated on for a benign disease was more frequent in euthyroid patients than in patients with hyperthyroidism [ 23 ] .…”
Section: ▼ Thyroid Cancer In Patients With Hyperthyroidismmentioning
confidence: 99%
“…The time of diagnosis of hyperthyroidism to thyroidectomy was not diff erent. However, Miccoli et al reported that, the diagnosis of incidental thyroid carcinoma in patients who were operated on for a benign disease was more frequent in euthyroid patients than in patients with hyperthyroidism [ 23 ] .…”
Section: ▼ Thyroid Cancer In Patients With Hyperthyroidismmentioning
confidence: 99%
“…However, it seems that, despite all efforts, small tumoral lesions might be left undiagnosed preoperatively in patients with multiple nodules. It is known that the majority of incidental thyroid carcinomas are PTC (21). Higher rate of PTC in EMNG might be attributed to the incidentality of nearly half the malignant lesions in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it is well known that frequency of thyroid procedures and incidental findings of thyroid cancer has been arising with an average rate of 10% [13,14]. Particularly, incidental finding of papillary microcarcinoma has been reported in a large number of patients undergoing thyroidectomy for benign thyroid disease, reaching up to 24% [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increased risk of non-parathyroid cancers in patients with pHPT has been reported in several studies [18]. Miccoli et al [13] reported thyroid malignancy as the most prevalent cancer among those patients in whom pHPT was [4,5,17,[19][20][21], others investigated several predisposing factors such as exposure to neck radiation, goitregenic effect and increased mitotic activity induced by hypercalcemia [22,23]. In addition, tumour-promoting effect of parathyroid hormone and subsequent genetic predisposition to new malignancies were also noted [16,24].…”
Section: Discussionmentioning
confidence: 99%